Assessment of vertical scar migration after classical abdominoplasty followed by lower abdominal flap fixation Avaliação da migração vertical da cicatriz pós-abdominoplastia clássica com fixação do retalho abdominal inferior - Paul Kaufmann; Luís Gustavo Moraes Prado; Vinícius Volpe D'Angieri Basile; Francesco Mazzarone; Ivo Pitanguy (Revista Brasileira de Cirurgia Plástica, 2011)
BACKGROUND: In plastic surgery, the postoperative scar is a frequent concern. It is very important for the surgeon to understand the natural evolution of the scar. The abdominoplasty scar has a natural tendency to move upwards over time. In this study, the extent of natural vertical scar migration after abdominoplasty was calculated and the effect of fixing the lower abdominal flap to prevent this rise was assessed. METHODS: This prospective and randomized study was conducted at the 38th Nursing service of Santa Casa de Misericórdia do Rio de Janeiro, during 2010, and included 20 female patients with an indication for abdominoplasty. The patients were randomly divided into two groups, A and B. Classical abdominoplasty was performed in group A patients, according to the technique recommended by Prof. Ivo Pitanguy. Patients in group B also underwent lower abdominal flap fixation by suturing of Scarpa's fascia and the rectus abdominis muscle aponeurosis. At both two weeks and six months after surgery, the distance of vertical scar movement was measured in 16 patients after application of exclusion criteria. The average vertical migration and the mean difference between the groups were calculated. RESULTS: The average difference between the groups in vertical migration throughout the scar was 0.4 cm, with a mean overall migration of 1.06 cm and 0.68 cm in groups A (control group) and B (cases with fixation), respectively. CONCLUSIONS: The scar formed after abdominoplasty undergoes vertical migration over time; this migration is decreased when the lower abdominal flap is fixed. The surgeon should be aware of scar migration for better planning of the incision location INTRODUÇÃO: Na cirurgia plástica, uma constante preocupação é a cicatriz pós-operatória. É muito importante para o cirurgião conhecer a evolução natural da cicatriz. A cicatriz de abdominoplastia tem a tendência natural de subir com o passar do tempo. Neste estudo, calculou-se a migração vertical natural da cicatriz pós-abdominoplastia, avaliando o efeito da fixação do retalho abdominal inferior na prevenção dessa ascensão. MÉTODO: Estudo prospectivo e randomizado, realizado na 38ª Enfermaria da Santa Casa de Misericórdia do Rio de Janeiro durante o ano de 2010, incluindo 20 pacientes do sexo feminino com indicação de abdominoplastia, divididas em dois grupos, A e B, aleatoriamente. Nas pacientes do grupo A, foi realizada abdominoplastia clássica, segundo técnica preconizada pelo Prof. Ivo Pitanguy, e no grupo B foi incluída a fixação do retalho abdominal inferior por meio de sutura interessando a fáscia de Scarpa e a aponeurose do músculo reto abdominal. Duas semanas e seis meses após a cirurgia, foi medida a distância vertical em 16 pacientes, após aplicação dos critérios de exclusão, calculando-se a média de migração vertical e a diferença média entre os dois grupos. RESULTADOS: A diferença média de migração vertical ao longo de toda a cicatriz foi de 0,4 cm, sendo a média geral de migração nos grupo A (controle) e B (casos com fixação) de 1,06 cm e 0,68 cm, respectivamente. CONCLUSÕES: A cicatriz pós-abdominoplastia sofre migração vertical ao longo do tempo, sendo menor quando o retalho inferior é fixado. O cirurgião deve estar ciente da migração sofrida pela cicatriz para melhor planejamento da posição de sua incisão